Epigenetic Modifications and Potential New Treatment Targets in Diabetic Retinopathy - Lorena Perrone; Carmela Matrone; Lalit P. Singh (Journal of Ophthalmology)
Retinopathy is a debilitating vascular complication of diabetes. As with other diabetic complications, diabetic retinopathy (DR) is characterized by the metabolic memory, which has been observed both in DR patients and in DR animal models. Evidences have provided that after a period of poor glucose control insulin or diabetes drug treatment fails to prevent the development and progression of DR even when good glycemic control is reinstituted (glucose normalization), suggesting a metabolic memory phenomenon. Recent studies also underline the role of epigenetic chromatin modifications as mediators of the metabolic memory. Indeed, epigenetic changes may lead to stable modification of gene expression, participating in DR pathogenesis. Moreover, increasing evidences suggest that environmental factors such as chronic hyperglycemia are implicated DR progression and may also affect the epigenetic state. Here we review recent findings demonstrating the key role of epigenetics in the progression of DR. Further elucidation of epigenetic mechanisms, acting both at the cis- and trans-chromatin structural elements, will yield new insights into the pathogenesis of DR and will open the way for the discovery of novel therapeutic targets to prevent DR progression.